The Associations between Self-Reported Exposure to the Chernobyl Nuclear Disaster Zone and Mental Health Disorders in Ukraine - Bolt, Matthew A.; Helming, Luralyn M.; Tintle, Nathan L. (Frontiers in Psychiatry, 2018)
Abstract Background: In 1986, Reactor 4 of the Chernobyl nuclear power plant near Pripyat, Ukraine exploded, releasing highly-radioactive materials into the surrounding environment. Although the physical effects of the disaster have been well-documented, a limited amount of research has been conducted on association of the disaster with long-term, clinically-diagnosable mental health disorders. According to the diathesis-stress model, the stress of potential and unknown exposure to radioactive materials and the ensuing changes to one’s life or environment due to the disaster might lead those with previous vulnerabilities to fall into a poor state of mental health. Previous studies of this disaster have found elevated symptoms of stress, substance abuse, anxiety, and depression in exposed populations, though often at a subclinical level. Materials and methods: With data from The World Mental Health Composite International Diagnostic Interview, a cross-sectional large mental health survey conducted in Ukraine by the World Health Organization, the mental health of Ukrainians was modeled with multivariable logistic regression techniques to determine if any long-term mental health disorders were association with reporting having lived in the zone affected by the Chernobyl nuclear disaster. Common classes of psychiatric disorders were examined as well as self-report ratings of physical and mental health. Results: Reporting that one lived in the Chernobyl-affected disaster zone was associated with a higher rate of alcohol disorders amongst men and higher rates of intermittent explosive disorders amongst women in a prevalence model. Subjects who lived in the disaster zone also had lower ratings of personal physical and mental health when compared to controls. Discussion: Stress resulting from disaster exposure, whether or not such exposure actually occurred or was merely feared, and ensuing changes in life circumstances is associated with to increased rates of mental health disorders. Professionals assisting populations that are coping with the consequences of disaster should be aware of possible increases in psychiatric disorders as well as poorer perceptions regarding personal physical and mental health.